2015
DOI: 10.1242/jcs.164004
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 suppresses embryo-epithelial juxtacrine communication at implantation by modulating maternal IGF1R

Abstract: Successful implantation requires the synchronization of viable embryonic development with endometrial receptivity. The mechanisms allowing for the initiation of crosstalk between the embryo and the endometrium remain elusive; however, recent studies have revealed that there are alterations in endometrial microRNAs (miRs) in women suffering repeated implantation failure and that one of the altered miRs is miR-145. We assessed the role of miR-145 and its target IGF1R, in early implantation. miR-145 overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 77 publications
1
55
0
Order By: Relevance
“…Accordingly, embryos that express miR-30d display increased adhesion to epithelial cells in vitro (Vilella et al, 2015). By contrast, there is evidence that a skewed miR profile in epithelial cells can impair receptivity (Kang et al, 2015).…”
Section: Box 2: Demonstrating Integrin Function In Implantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, embryos that express miR-30d display increased adhesion to epithelial cells in vitro (Vilella et al, 2015). By contrast, there is evidence that a skewed miR profile in epithelial cells can impair receptivity (Kang et al, 2015).…”
Section: Box 2: Demonstrating Integrin Function In Implantationmentioning
confidence: 99%
“…It may be that there is a complex interplay between integrins and other cell surface factors. Indeed, a number of components of the uterine cell surface have functional roles in implantation and interact with αv integrins, including CD98 (officially known as SLC3A2) (Domínguez et al, 2010), the tetraspanin CD9 (Domínguez et al, 2010;Liu et al, 2006;Wynne et al, 2006), the dipeptidyl peptidase CD26 (officially known as DPP4) (Shimomura et al, 2006), the epidermal growth factor (EGF)-domaincontaining glycoprotein MFG-E8 (Schmitz et al, 2014), the IGF receptor (Fujita et al, 2013;Kang et al, 2015), galectin 3 (Lei et al, 2009;Yang et al, 2012) and galectin 15 (Lewis et al, 2007).…”
Section: Box 2: Demonstrating Integrin Function In Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are secreted by cells and incorporated into microvesicles or associated with proteins that protect them from RNase degradation, endowing them with a long half-life (Turchinovich et al, 2011;Yoshizawa and Wong, 2013). These molecules have been implicated in the regulation of the WOI (Altmäe et al, 2010;Kuokkanen et al, 2010;Ng et al, 2013;Sha et al, 2011), decidualization (Estella et al, 2012a,b) and embryo development in humans (Mincheva-Nilsson and Baranov, 2010), and, more recently, embryo implantation in mice (Chen et al, 2015;Kang et al, 2015;Liu et al, 2013;Revel et al, 2011). In the present study, we aimed to elucidate the role of and mechanisms by which maternal miRNAs secreted into the EF act as transcriptomic regulators of the reprogramming of pre-implantation embryos by the maternal intrauterine environment.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies reported that miR-30b, miR-30d, and -miR-494 are differentially expressed in pre-receptive and receptive endometria in human [10], suggesting that miRNAs played important roles in gene reprogramming during the formation of endometrial receptivity. In addition, miR-145 suppresses embryo-epithelial juxtacrine communication in the procession of embryo attachment by modulating the expression levels of IGF1R in endometria during WOI [11]. Together with its family members (miR-96 and miR-183), miR-182 was described in mouse neurosensory cells, specifically in the retina, inner ear, and dorsal root ganglia [1214].…”
Section: Introductionmentioning
confidence: 99%